ECOLOGY AND FAUNA OF THE SPECIES BELONGING TO THE FAMILY COLUBRIDAE OF KASHKADARYA REGION - Yangiboyev E. Ch.; Rakhimov M. Sh (Galaxy International Interdisciplinary Research Journal, 2021)
This article provides informations about the ecology and fauna of the family Colubridae in the Kashkadarya region. Herpetofauna of Kashkadarya region has not been studied scientifically for several decades. Our data were collected in the spring and summer of 2018-2020 and in April-May 2021.